(untitled) (Desarrollo, Estado y Espacio, 2024)
In this paper we reflect on processes of commodification of natures and cultures within the framework of global capitalism. From a multi-scale perspective, the global-local coupling of socio-technical systems takes shape in the territories, as moments articulated in networks of social relations and agreements in interrelation with materialities. There complex normative-technical plots are brought into play that we seek to reveal, since it is through them that the processes of commodification and resistance are effectuated and operate in a systemic way, in close interdependence with territorial transformations. From the perspective of the Political Ecology of water, we analyze in a comparative way two cases of socio-environmental conflict processes due to water contamination in Argentina: one due to pesticides in Lobos (Buenos Aires) and the other due to algal blooms with cyanobacteria in Concepción del Uruguay (Entre Ríos). We wonder how and with what effects the norms and technical objects mediate in the processes of commodification of natures and cultures in which contamination and deterioration of water bodies are identified, and what are the transformations and territorial disputes associated with them? The methodological design of the research is qualitative and pursues a comparative analysis between the two case studies. The sources of information were interviews with key informants, participant observations, and secondary sources. Based on the analysis of the networks of relationships around certain normative-technical objects, we reflect on the condition of visibility/invisibility of the processes of deterioration in water bodies and their relationship with public policies and development models.